Comparative study of U- and U4-split-ring resonator-based metasurfaces for sensing in near- and mid-infrared region - Suo, Fei (2022)
We report a detailed comparative investigation of resonance behaviors and sensing capability of gold U-shape spilt-ring resonator (U-SRR) and fourfold rotated SRR (U4-SRR) metasurfaces in near- and middle-infrared (IR) range. All the resonant modes of the U4-SRR metasurfaces occur at longer wavelengths compared to the U-SRR metasurfaces with the same U size. Stronger field intensities are observed in all the three resonance modes of the U4-SRR metasurfaces and the intensity in the fundamental magnetic (m 0) mode is almost three times of that of U-SRR metasurface under unpolarized incidence. All the three peak resonance wavelengths shift to longer wavelengths and the sensitivity increases with the increase of U size. A sensitivity of 642 nm RIU-1 is obtained in the U4-SRR metasurface for unpolarized incidence. This provides an excellent candidate for high performance sensing in the near- and mid-IR regions without polarization concern.